Unraveling the role of aurora A beyond centrosomes and spindle assembly: implications in muscle differentiation. Issue 1 (11th July 2018) - Dhanasekaran, Karthigeyan; Bose, Arnab; Rao, Vinay J.; Boopathi, Ramachandran; Shankar, Shilpa Rani; Rao, Vinay Kumar; Swaminathan, Amrutha; Vasudevan, Madavan; Taneja, Reshma; Kundu, Tapas K.
ABSTRACT: Aurora kinases are critical mitotic serine/threonine kinases and are often implicated in tumorigenesis. Recent studies of the interphase functions for aurora kinase (Aurk)A have considerably expanded our understanding of its role beyond mitosis. To identify the unknown targets of AurkA, we used peptide array‐based screening and found E2F4 to be a novel substrate. Phosphorylation of E2F4 by AurkA at Ser75 regulates its DNA binding and subcellular localization. Because E2F4 plays an important role in skeletal muscle differentiation, we attempted to gain insight into E2F4 phosphorylation in this context. We observed that a block in E2F4 phosphorylation retained it better within the nucleus and inhibited muscle differentiation. RNA sequencing analysis revealed a perturbation of the gene network involved in the process of muscle differentiation and mitochondrial biogenesis. Collectively, our findings establish a novel role of AurkA in the process of skeletal muscle differentiation.—Dhanasekaran, K., Bose, A., Rao, V. J., Boopathi, R., Shankar, S. R., Rao, V. K., Swaminathan, A., Vasudevan, M., Taneja, R., Kundu, T. K. Unravelling the role of aurora A beyond centrosomes and spindle assembly: implications in muscle differentiation. FASEB J. 33, 219–230 (2019). www.fasebj.org